Bank Survival Around the World: A Meta-Analytic Review - Evzen Kocenda; Ichiro Iwasaki (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Bank survival is essential to economic growth and development because banks mediate the financing of the economy. A bank's overall condition is often assessed by a supervisory rating system called CAMELS, an acronym for the components Capital adequacy, Asset quality, Management quality, Earnings, Liquidity, and Sensitivity to market risk. Estimates of the impact of CAMELS components on bank survival vary widely. We perform a meta-synthesis and meta-regression analysis (MRA) using 2120 estimates collected from 50 studies. In the MRA, we account for uncertainty in moderator selection by employing Bayesian model averaging. The results of the synthesis indicate an economically negligible impact of CAMELS variables on bank survival; in addition, the effect of bank-specific, (macro)economic, and market factors is virtually absent. The MRA and a test for publication selection bias produce findings consistent with the synthesis results. Moreover, best practice estimates show a small economic impact of CAMELS components and no impact of other factors. The study concludes that caution should be exercised when using CAMELS rating to predict bank survival or failure.
Keywords: C12; D22; G21; G33; 330; bank survival; bank failure; CAMELS; meta-analysis; publication selection bias